A recepção da psicanálise em Frantz Fanon : uso e implicação para o campo psicanalítico - Pedro Donizete Ferreira (2022)
In this work, I investigate Frantz Fanon’s reception of psychoanalytic theory. Privilege, thus, his two initial essays: the thesis for the exercise of medicine, defended in 1951 and the essay Black skin, White Masks. For this, I developed two articles: in the first, through the concepts of alienation and complex, I approach Fanon’s relationship with Freud, Adler, Jung and Lacan. In the second, I deal especially with the complexes of dependence and inferiority, worked by Mannoni in Psychologie de la colonisation [Psychology of Colonization] and criticized by Fanon in Black Skin. Moreover, I wonder if Fanon’s reception could have any implication for the psychoanalytic field. Hence, I draw two consequences: the articulation between the clinic and the social transformation, where the clinic is the politics itself and vice-versa; and the interweaving of the theory and the psychoanalytic clinic as the foundation for an anti-racist praxis.